Influence of plant parts on in vitro dry matter disappearance of forage sorghum silages - White, J.; Bolsen, K.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Five mid- to late- season forage sorghum hybrids were used to plot the changes in silage in vitro dry matter disappearance (IVDMD) when their proportions of grain, leaf, sheath, and stalk were altered. The average IVDMD of the parts were: grain 76.9%, leaf 57.7%, sheath 52.7%, and stalk 60.8 percent. The grain proportion had a large positive effect on silage IVDMD dynamics, whereas the sheath plant part had a negative effect.
Keywords: Beef; In vitro; Dry matter; Sorghum